Draft Genome Sequence of a Diarrheagenic Morganella morganii Isolate - Singh, Pallavi (Genome Announc, 2015)
This is a report of the whole-genome draft sequence of a diarrheagenic Morganella morganii isolate from a patient in Michigan, USA. This genome represents an important addition to the limited number of pathogenic M. morganii genomes available.